2017
DOI: 10.1101/144501
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SCENIC: Single-cell regulatory network inference and clustering

Abstract: Single-cell RNA-seq allows building cell atlases of any given tissue and infer the dynamics of cellular state transitions during developmental or disease trajectories. Both the maintenance and transitions of cell states are encoded by regulatory programs in the genome sequence. However, this regulatory code has not yet been exploited to guide the identification of cellular states from single-cell RNA-seq data. Here we describe a computational resource, called SCENIC (Single Cell rEgulatory Network Inference an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
1,482
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 886 publications
(1,502 citation statements)
references
References 101 publications
11
1,482
0
2
Order By: Relevance
“…Significantly deregulated genes from Aibar et al () were adopted as shown in Appendix Table S5 from the original publication. Normalized data from Shoshan et al () were downloaded from NCBI GEO (accession GSE76541), and hits were selected according to adjusted P ‐values (Benjamini–Hochberg procedure, FDR = 0.05).…”
Section: Methodsmentioning
confidence: 99%
“…Significantly deregulated genes from Aibar et al () were adopted as shown in Appendix Table S5 from the original publication. Normalized data from Shoshan et al () were downloaded from NCBI GEO (accession GSE76541), and hits were selected according to adjusted P ‐values (Benjamini–Hochberg procedure, FDR = 0.05).…”
Section: Methodsmentioning
confidence: 99%
“…While there exist GRN inference methods that were specifically developed for scRNA‐seq data (SCONE: Matsumoto et al , ; PIDC: Chan et al , ; SCENIC: Aibar et al , ), a recent comparison has shown both bulk and single‐cell methods to perform poorly on these data (Chen & Mar, ). GRN inference methods may still offer valuable insights to identify causal regulators of biological processes, yet we recommend that these methods be used with care.…”
Section: Introductionmentioning
confidence: 99%
“…The adaptation of gene expression is the result of altered regulatory activity; therefore, we aimed to characterize the TFs involved in the phenotype shift. For this, SCENIC was used to map gene regulatory network activity and cell states. This revealed three robust cell states corresponding to the two culture conditions and cells undergoing mitosis (Figure Ai).…”
Section: Resultsmentioning
confidence: 99%